Incidence and Types of Congenital Heart Diseases among Children in Sulaimani Governorate - Kamal, Niaz; Othman, Nasih; Salih, Aso (Kurdistan Journal of Applied Research, 2017)
Congenital heart diseases (CHD) are common causes of cardiovascular morbidity and mortality among young children and adolescents. It is the most common form of structural congenital defects. Little is known about incidence and type of these disorders in Sulaimani. Therefore, this study was undertaken to determine the incidence of congenital heart diseases and their types in Sulaimani Governorate. The study was conducted in Sulaimani Pediatric Teaching Hospital and the Maternity Hospital during January 2015 to December 2016. A sample of 400 consecutive cases of CHD in children aged 0-12 years was recruited attending the echocardiographic department of the hospital for diagnosis or follow-up purposes. Demographic data was collected through a face-to-face interview with the mothers of cases. A total number of new live births for 2015-2016 and those with congenital heart diseases were obtained from the medical records of the department of statistics of Sulaimani Maternity Teaching Hospital. The overall incidence of all types of congenital heart diseases was 1.7/1000, 1.6/1000 live births for the year 2015 and 2016 respectively. There was a statistically significant difference in incidence between males and females over the two years, male to female risk ratio 1.83 (95% CI 1.09-3.14, p 0.007). The commonest types of cyanotic congenital heart diseases were tetralogy of Fallot (38.9% of all cyanotic defects), complete atrioventricular canal (22.1%), and transposition of great arteries (18.2%), while the most common types of non-cyanotic congenital heart disease were atrial septal defect (34.1% of all non-cyanotic defects), ventricular septal defect (31.6%), and the other defects are less common. In conclusion, tetralogy of Fallot, atrial septal defects, and ventricular septal defects are the commonest congenital heart deformities in Sulaimani Governorate; the incidence is lower than other countries but this could be an underestimation.